Greed as a factor of family and organizational conflicts - Trofimov, Andrii; Skrypka, Anastasiia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article considers the study of the peculiarities of greed as a factor in family and organizational conflicts, conducted an empirical study and presents the results of an empirical study on the manifestation of greed as a factor in family and organizational conflicts. The links between greed and indicators that reflect family and organizational conflicts have been identified and a conceptual model has been developed that reflects the content of the phenomenon under study. A proven greed reduction training has been developed that has been shown to be effective. Greed as a factor of conflict is manifested from and as resources to solve the problem, and as the destruction of relationships in the team, in families. The basis of dynamic changes in society is conflict. One of the psychological causes of destructive conflict in organizations and families is greed. Greed has an impact on all spheres of human life, because it is an individual property, has specific characteristics of its manifestation, which are not always well related to the social environment and other people in general, greed will inevitably manifest itself in interaction with others, which can lead to various conflicts.The results of the study and the identified trends of greed in family and organizational conflicts confirm the need to update actions aimed at creating theoretical concepts, conceptual model of greed as a factor in conflict in different environments, development of specialized training, developmental training, corrective programs and measures to reduce greed as factor of family and organizational conflicts.
Keywords: disposition; greed; conflict; organization; environment; family